Genetics of Quantitative Phenotype of African Fan Shrimp (Atya gabonensis) from Lower River Benue, Makurdi, Nigeria Using Principal Component Analysis - Mamndeyati, Uruku Ndekimbe; Rose, Ameh Oyibinga; Solomon, Gabriel Shola (Darul Yasin Al Sys, 2025)
The African fan shrimp (Atya gabonensis), a non-clawed, filter-feeding decapod of ecological and nutritional importance, remains understudied regarding its population structure and phenotypic variability in Nigerian freshwater ecosystems. This study assessed quantitative phenotypic traits and inferred population structure of A. gabonensis from the Lower River Benue, Makurdi, Nigeria, using Principal Component Analysis (PCA). One hundred adult specimens were measured for 14 morphometric traits, including total length, carapace dimensions, and abdominal parameters. After standardizing data via allometric transformation, PCA was performed to identify key contributors to phenotypic variation. Data suitability was confirmed (KMO = 0.73, Bartlett’s test p < 0.001). The first four principal components, with eigenvalues greater than one, explained 75.65% of total variance. PC1 (32.31%) was dominated by total length, standard length, and body weight, reflecting overall body size. PC2 (19.91%) emphasized carapace and abdominal length, indicating internal body capacity variation. PC3 (11.89%) and PC4 (11.54%) represented differences in gut and carapace width, respectively, suggesting morphological variation linked to environmental adaptation or sexual dimorphism. These morphometric patterns reveal significant phenotypic variability within the population, providing insights into potential genetic divergence and local adaptation. The findings offer foundational data to support species management, aquaculture development, and conservation strategies. This study demonstrates the efficacy of PCA in elucidating key phenotypic traits and highlights the value of integrating morphometric and genetic analyses for comprehensive crustacean stock assessments.